Semi-analytical and experimental study on array of elastic circular floaters vertical motions in regular sea waves. (1st December 2020) - Gharechae, Ataollah; Ketabdari, Mohammad Javad; Kitazawa, Daisuke; Li, Qiao
Abstract: In this paper, a semi-analytical method was developed to find the vertical accelerations of array of semi-submerged elastic circular floaters in regular waves. In this process, it was assumed that the fluid is inviscid, incompressible, and irrational flow. Furthermore, incident wavelength was relatively large in comparison to the floaters cross-section. Using slender body theory and matched asymptotic expansions, the inner solution close to the body section composed of suitable radiation solution at large distance from floaters. By this method, the governing equation on the diffracted wave of each floater was expressed as a simple function of Fourier modes of incident waves. Finally, using linear wave theory, the relationship between the incident, radiated, and diffracted waves on an array of floaters was established in Fourier modes. The model results demonstrate good agreement with those of the boundary element method. A series of experimental tests were also performed for model validation. The results show that as the wavenumber increases, the floater hydro-elastic interaction is becoming important. Furthermore, the floaters on upstream have larger significant vertical motions in comparison to a single floater in waves. Highlights: Matched asymptotic expansion was used to express wave interaction with array of elastic tori. At wavenumber ϑ a > 0.15, the upstream torus has larger accelerations than a single torus in waves. The upstream floater encounters up to 35% larger accelerations than a single floater. For array of tori, doubling bending stiffness reduces the peak of acceleration by 10%. An increase of 25% in the relative dimension ( a / c ) reduces the acceleration by 8%.